1983
DOI: 10.1159/000260716
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Clinical Effect of Monofluorophosphate in the Presence of Sodium Lauryl Sulphate

Abstract: It was shown that addition of 2% sodium lauryl sulphate to a 3% aqueous solution of sodium monofluorophosphate reduced the caries-inhibiting potential of the monofluorophosphate solution significantly, when this solution was applied topically at fortnightly intervals. It is suggested that this may be due to enzyme inhibition by the lauryl sulphate, denaturing bacterial enzymes in the oral cavity which would otherwise release free fluoride from the monofluorophosphate molecule. Almost all commercial toothpaste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…While SDS appears capable of impacting fluoride efficacy [Melsen and Rolla, 1983;Barkvol et al, 1988;Robinson et al, 2006;Zero, 2006;Vogel et al, 2015], this study did not find any meaningful difference in the effect of the 2 surfactant systems employed (which both contained a substantial level of SDS) on any of the study measures, suggesting that neither the chemical differences (varying concentration of SDS and presence or absence of tegobetaine cosurfactant) nor physical differences (different foaming of the 2 zinc dentifrices) meaningfully affected fluoride efficacy in this study.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…While SDS appears capable of impacting fluoride efficacy [Melsen and Rolla, 1983;Barkvol et al, 1988;Robinson et al, 2006;Zero, 2006;Vogel et al, 2015], this study did not find any meaningful difference in the effect of the 2 surfactant systems employed (which both contained a substantial level of SDS) on any of the study measures, suggesting that neither the chemical differences (varying concentration of SDS and presence or absence of tegobetaine cosurfactant) nor physical differences (different foaming of the 2 zinc dentifrices) meaningfully affected fluoride efficacy in this study.…”
Section: Discussioncontrasting
confidence: 53%
“…They also have the potential to modulate the physical state of the dentifrice as it contacts the enamel surface (e.g., via foaming) and thereby influence fluoride effectiveness. Some data indicate that sodium dodecyl sulfate (SDS, also known as sodium lauryl sulfate), an anionic surfactant commonly used in dentifrices, impedes delivery of fluoride to enamel [Melsen and Rolla, 1983;Barkvol et al, 1988;Zero, 2006], while other studies suggest it can assist penetration of fluoride through the plaque matrix [Robinson et al, 2006;Vogel et al, 2015].…”
mentioning
confidence: 99%
“…Mellberg and Chomicki [1984] found that sodium lau ryl sulfate did not reduce the fluoride uptake in artifi cial caries lesions from sodium monofluorophos-phate dentifrices in vivo. On the other hand, Melsen and Rolla [1983] showed that sodium lauryl sulfate re duced the clinical effect of topically applied sodium monofluorophosphate and there is reason to assume that sodium lauryl sulfate affects the deposition of fluoride from sodium monofluorophosphate on enamel in the same way as from NaF [Barkvoll et al, 1987].…”
Section: Solubility O F Caf2 In Sodium Lauryl Sulfate Solutionsmentioning
confidence: 99%
“…When applied topically at fort nightly intervals, it has been shown that addition of sodium lauryl sulfate to an aqueous solution of so dium monofluorophosphate reduces the caries-inhib iting potential of the fluoride solution significantly [Melsen and Rolla, 1983]. Gron and Caslavska [1983] found that sodium lauryl sulfate in fluoride solutions for topical application did not interfere with deposi tion of firmly bound fluoride in enamel.…”
mentioning
confidence: 99%
“…It is acknowledged that excipients in a toothpaste formulation could reduce the anticaries performance [33]. Similar interactions could affect the anticaries performance of mouthrinse.…”
Section: Discussionmentioning
confidence: 99%